Pendampingan Optimalisasi Penggunaan Input Produksi Hortikultura Organik di Gumi Alami Farm: Pengabdian - Yuniti, I Gusti Ayu Diah; Ni Putu Sukanteri; I Made Budiasa (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
Organic horticulture is one of the important sectors in supporting food security, environmental sustainability, and improving farmer welfare. The purpose of implementing community service is to increase farmer knowledge in managing horticultural products, improve farmer skills in providing input for horticultural commodity production, especially organic fertilizers. And improve the quality of products to be marketed. The implementation of community service is carried out at Gumi Alami Farm, Baturiti Tabanan Bali. Community service activities for organic horticulture farmers are carried out through several stages, namely socialization, training and mentoring. Community service activities are carried out in three stages, namely socialization, training and mentoring which show that farmers have the knowledge and skills to increase the use of organic inputs in horticultural production by 80%.